Book Review: Ramachandra Guha, Democrats and Dissenters. Issue 2 (August 2017) - Yadav, Vivek Kumar; Kumar, Bharath
Ramachandra Guha, Democrats and Dissenters . Gurugram: Penguin Random House India Private Limited, 2016, ₹699, 352 pp., ISBN 978-0-670-08936-9.